2003
DOI: 10.1002/ange.200350956
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembled Receptors that Stereoselectively Recognize a Saccharide

Abstract: Süße Auswahl: Ein Rezeptor, der die stereoselektive Erkennung von Zuckern ermöglicht, bildet sich durch Selbstorganisation von Wasserstoffbrücken. Der Rezeptor liegt als racemisches Gemisch von P‐ und M‐Helices vor; Zugabe einer chiralen Gastverbindung verschiebt das Gleichgewicht zugunsten eines der Enantiomere (siehe Schema).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
70
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 63 publications
0
70
0
Order By: Relevance
“…Thus, a supramolecular self-assembled system is regarded as one of the most suitable media for chiral amplification, in which chiral information of the chiral sergeant component is transferred to the soldier-based aggregate via the noncovalent interactions and amplified to control the entire supramolecular chirality. The chiral aggregates produced by chiral amplification would provide an attractive medium for asymmetric reactions [15] and chiral recognition, [16] as well as applications as nanoscale functional materials with piezoelectric, pyroelectric, and ferroelectric properties, [17] although the low stability of the noncovalent architecture should be overcome by using chemical modification such as covalent fixation. Recently, Meijer et al reported fixation of a chiral structure created in a columnar-type helical aggregate by a chiral-amplification method.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a supramolecular self-assembled system is regarded as one of the most suitable media for chiral amplification, in which chiral information of the chiral sergeant component is transferred to the soldier-based aggregate via the noncovalent interactions and amplified to control the entire supramolecular chirality. The chiral aggregates produced by chiral amplification would provide an attractive medium for asymmetric reactions [15] and chiral recognition, [16] as well as applications as nanoscale functional materials with piezoelectric, pyroelectric, and ferroelectric properties, [17] although the low stability of the noncovalent architecture should be overcome by using chemical modification such as covalent fixation. Recently, Meijer et al reported fixation of a chiral structure created in a columnar-type helical aggregate by a chiral-amplification method.…”
Section: Introductionmentioning
confidence: 99%
“…Let us assume, as is found in one-dimensional aggregates, 34 that the two porphyrin molecules are stacked with their principal symmetry axes aligned with each other and with the direction of intermolecular displacement; for simplicity let us also assume plane polarized laser light propagating along this z direction. References to the character tables for D 2h and D 4h show that in this fixed chromophore case, the only nonzero components of the tensor of either species will be ␣ xx and ␣ yy .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the synthesis of a given enantiomer can be performed in a stereospecific way. 105,106 The removal of the diacids led also to the formation of enantiopure assemblies. Diastereomeric excess in both the cases was high (de 96%).…”
Section: Formation Of Chiral Structures In a Non-covalent Waymentioning
confidence: 99%